Пам’яті професора М.М. Братичака - katalizadmin, ... (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2023)
In memory of Professor Michael M. Bratychak